Impact of Source Control in Patients With Severe Sepsis and Septic Shock*. Issue 1 (January 2017) - Martínez, María Luisa; Ferrer, Ricard; Torrents, Eva; Guillamat-Prats, Raquel; Gomà, Gemma; Suárez, David; Álvarez-Rocha, Luis; Pozo Laderas, Juan Carlos; Martín-Loeches, Ignacio; Levy, Mitchell M.; Artigas, Antonio
Abstract : Objectives: Time to clearance of pathogens is probably critical to outcome in septic shock. Current guidelines recommend intervention for source control within 12 hours after diagnosis. We aimed to determine the epidemiology of source control in the management of sepsis and to analyze the impact of timing to source control on mortality. Design: Prospective observational analysis of the Antibiotic Intervention in Severe Sepsis study, a Spanish national multicenter educational intervention to improve antibiotherapy in sepsis. Setting: Ninety-nine medical-surgical ICUs in Spain. Patients: We enrolled 3, 663 patients with severe sepsis or septic shock during three 4-month periods between 2011 and 2013. Interventions: Source control and hospital mortality. Measurements and Main Results: A total of 1, 173 patients (32%) underwent source control, predominantly for abdominal, urinary, and soft-tissue infections. Compared with patients who did not require source control, patients who underwent source control were older, with a greater prevalence of shock, major organ dysfunction, bacteremia, inflammatory markers, and lactic acidemia. In addition, compliance with the resuscitation bundle was worse in those undergoing source control. In patients who underwent source control, crude ICU mortality was lower (21.2% vs 25.1%; p = 0.010); after adjustment for confounding factors, hospital mortality was also lower (odds ratio, 0.809 [95% CI, 0.658–0.994]; p = 0.044). In this observational database analysis, source control after 12 hours was not associated with higher mortality (27.6% vs 26.8%; p = 0.789). Conclusions: Despite greater severity and worse compliance with resuscitation bundles, mortality was lower in septic patients who underwent source control than in those who did not. The time to source control could not be linked to survival in this observational database. Abstract : Supplemental Digital Content is available in the text.